An ARHGAP25 variant links aberrant Rac1 function to early-onset skeletal fragility - Mäkitie Riikka E.; Henning Petra; Jiu Yaming; Kämpe Anders; Kogan Konstantin; Costantini Alice; Välimäki Ville-Valtteri; Medina-Gomez Carolina; Pekkinen Minna; Salusky Isidro B.; Schalin-Jäntti Camilla; Haanpää Maria K.; et al. (Blackwell Publishing Ltd, 2022)
Ras homologous guanosine triphosphatases (RhoGTPases) control several cellular functions, including cytoskeletal actin remodeling and cell migration. Their activities are downregulated by GTPase-activating proteins (GAPs). Although RhoGTPases are implicated in bone remodeling and osteoclast and osteoblast function, their significance in human bone health and disease remains elusive. Here, we report defective RhoGTPase regulation as a cause of severe, early-onset, autosomal-dominant skeletal fragility in a three-generation Finnish family. Affected individuals (n = 13) presented with multiple low-energy peripheral and vertebral fractures despite normal bone mineral density (BMD). Bone histomorphometry suggested reduced bone volume, low surface area covered by osteoblasts and osteoclasts, and low bone turnover. Exome sequencing identified a novel heterozygous missense variant c.652G>A (p.G218R) in ARHGAP25, encoding a GAP for Rho-family GTPase Rac1. Variants in the ARHGAP25 5′ untranslated region (UTR) also associated with BMD and fracture risk in the general population, across multiple genomewide association study (GWAS) meta-analyses (lead variant rs10048745). ARHGAP25 messenger RNA (mRNA) was expressed in macrophage colony-stimulating factor (M-CSF)–stimulated human monocytes and mouse osteoblasts, indicating a possible role for ARHGAP25 in osteoclast and osteoblast differentiation and activity. Studies on subject-derived osteoclasts from peripheral blood mononuclear cells did not reveal robust defects in mature osteoclast formation or resorptive activity. However, analysis of osteosarcoma cells overexpressing the ARHGAP25 G218R-mutant, combined with structural modeling, confirmed that the mutant protein had decreased GAP-activity against Rac1, resulting in elevated Rac1 activity, increased cell spreading, and membrane ruffling. Our findings indicate that mutated ARHGAP25 causes aberrant Rac1 function and consequently abnormal bone metabolism, highlighting the importance of RhoGAP signaling in bone metabolism in familial forms of skeletal fragility and in the general population, and expanding our understanding of the molecular pathways underlying skeletal fragility.